Social Support and Resilience as Mediators Between Stress and Life Satisfaction Among People With Substance Use Disorder in China - Yang, Chunyu; Xia, Mengfan; Han, Mengmeng; Liang, Ying (Frontiers in Psychiatry, 2018)
This study investigated the potential mediating roles of resilience and social support in the relationship between stress and life satisfaction. A total of 426 individuals who have substance use disorder from the Shifoushi and Dalianshan rehabilitation facilities in China participated in the study. They were tested using the Perceived Stress Scale, Multidimensional Scale of Perceived Social Support, Connor–Davidson Resilience Scale, and Satisfaction with Life Scale. Results showed that the serial multiple mediation of social support and resilience in the relationship between stress and life satisfaction was significant. Furthermore, the findings corroborate the important roles of perceived social support and resilience in alleviating stress. Finally, we discussed ways to enhance the life satisfaction for individuals who have substance use disorder and analyzed the limitations of this study.